Risk Factors for Child Tuberculosis in Ambon City in 2019 - Ivy Violan Lawalata; Bellytra Talarima (Newinera Publisher, 2020)
The percentage of TB globally reaches 6% (530,000 TB patients children/year) while the death of children (with negative HIV status) suffering from TB reaches 74,000 deaths/year or with a percentage of about 8% of the total deaths caused by TB (TB Control Guidelines, 2014 ). The number of TB cases in children in Ambon City in 2018 was 220 cases in 22 Puskesmas, the highest cases of TB in children were in three Puskesmas including Puskesmas Ch.M. Tiahahu, 16 TB cases in children, Air Salobar Health Center with 5 TB cases for children and Rijali Health Center with 1 TB case for children. This study aims to determine whether BCG immunization, nutritional status, LBW, smoking, and household contacts are risks of TB in children in Ambon City in 2019. This type of research uses retrospective correlation analytical case control studies design that identifies patients and their effects or diseases. certain (cases) and groups without cases. The sample in this study consisted of 22 cases of TB for children under five and 64 controls for children under five. The case sampling technique was the total sampling, the comparison of cases and controls was 1: 2. The results of the analysis based on 95% CI obtained a value of OR = 0.101 with a CI 95% LL - UP 0.010-1.024, nutritional status OR = 1.761 with 95% CI LL - UP 0.524-5.921, LBW OR = 3.492 with 95% CI LL - UP 1,141-10,688, smoking behavior OR value = 0.536 with CI 95% LL - UP 0.189-1.521 and household contacts determine the value OR = 31.00 with CI 95% LL - UP 6.029-159,398.